INTERAKSI CALON PENGANTIN PASCA PERTUNANGAN (Studi Kasus di Desa Bandung kecamatan Diwek Kabupaten Jombang) - Emi Kholilah; Ahmad Ubaydi Hasbillah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The engagement period is a time when the prospective bride and groom get to know each other so that they gain the stability to carry out the wedding. During this period, there are other things that the prospective bride and groom must pay attention to, namely regarding social etiquette during the engagement period. In principle, the proposal does not have legal consequences, so those who are engaged are still prohibited from carrying out activities together until they have entered into a marriage contract. Unless it is permitted, the presence of a mahram can prevent them from committing immorality.The research in this thesis uses field research methods, with a qualitative approach and then analyzed using descriptive analysis.The residents of Bandung Village had widely varying reactions to the study's findings. Engagment, according to some in Bandung Village, is a powerful bonding experience that allows both partners to learn more about each other. Because they are already engaged, the proposal will certainly marry their daughter, and they won't tamper with their fiancé, so they may speak to each other without a mahram, go out together, and make peace. This gives them a chance to get to know their possible partner better. On the other hand, there are those who believe that couples should keep their distance after an engagement and that they should only become closer via their parents or mahram if they really feel the need. Hence, the current regulations of Islamic law need to be reinforcing in order to prevent young people, including engaged couples and other adolescents, from making social faux pas.